THE INFLUENCE OF PRICE ND SERVICE QUALITY ON PURCHASE DECISIONS AT TOKO MARANNU IN GOWA REGENCY - Rusni Andriani Rani; Muhammad Jufri; Asmayanti; Agus Syam; Sumiati Tahir (BORJUIS: JURNAL OF ECONOMY, 2025)
Pricing strategy and quality service play a crucial role in attracting consumer interest and encouraging purchasing decisions. Competitive prices that match product quality will create a positive perception among consumers, while good service will provide a pleasant shopping experience and build consumer trust. This study aims to determine the influence of Price and Service Quality on Purchase Decisions at Toko Marannu. The research uses a descriptive quantitative approach, with the population consisting of all customers who shop at Toko Marannu. Data were collected through the distribution of questionnaires using the Maholtra formula for sampling, with a total of 65 respondents. Data analysis was performed using multiple linear regression with SPSS. The results show that: 1) the Price variable has a significant effect on Purchase Decisions; 2) the Service Quality variable has a significant effect on Purchase Decisions; and 3) Price and Service Quality simultaneously have a significant effect on Purchase Decisions. The Adjusted R Square value is 50.4%, indicating that Price and Service Quality explain 50.4% of the variance in Purchase Decisions, while the remaining 49.6% is explained by other variables not examined in this study.